Reportagem orientada pelo clique: audiência enquanto critério de seleção da notícia online - Hatzigeorgiou, Ricardo Fotios (2018)
The fragmentation of the production and consumption of news on the Internet triggers the need for more and better processes to measure audience habits to guide the journalistic work. This new skill in the professional routine – which emerges from the increase in “big data” gathering and analyzes associated with the complexity of the publishing systems, also called CMS (Content Management System) – allows the journalist to follow all stages of news spreading in terms of quantity of accesses as well as public engagement. In this research, called ROC (Portuguese acronym for Click-Oriented News Reporting), we sought to analyze the impact that the knowledge of these consumption habits exerts on the deontology of cyberjournalism, more specifically, on the selection of guidelines and highlights in editorial homepages of websites and news portals.